2020
DOI: 10.1097/fbp.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of baseline locomotion and other behavioral traits in a common marmoset model of Parkinson's disease established by a single administration regimen of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine: providing reference data for efficacious preclinical evaluations

Abstract: Baseline locomotion and behavioral traits in the common marmoset Parkinson's disease model were examined to provide basic information for preclinical evaluations of medical treatments. A single regimen of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine at a cumulative dose of 5 mg/kg as the free base over three consecutive days was administered subcutaneously to 10 marmosets. Data obtained from these marmosets were compared to pre-1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine levels or 1-methyl-4-phenyl-1,2,3,6-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…They have also established care protocols for the acute toxic phase that include oral administration of nutrient solution and subcutaneous infusion for hydration, as well as protocols for behavioral measurements, such as automated counting of spontaneous motor activity and dysfunction scoring systems. MPTP-treated marmosets exhibited major signs of PD, such as immobility (decrease of spontaneous motor activity), tremor, muscle rigidity, and postural dysfunction, in conjunction with dopaminergic degeneration of the substantia nigra [ 22 , 24 ]. Furthermore, in MRI studies of MPTP-treated marmosets, voxel-based morphometry has revealed a decreased local tissue volume in the substantia nigra, and diffusion-tensor imaging demonstrated fiber loss in the nigrostriatal pathway [ 25 , 26 ].…”
Section: Experimental Disease Models For Translational Research Using...mentioning
confidence: 99%
“…They have also established care protocols for the acute toxic phase that include oral administration of nutrient solution and subcutaneous infusion for hydration, as well as protocols for behavioral measurements, such as automated counting of spontaneous motor activity and dysfunction scoring systems. MPTP-treated marmosets exhibited major signs of PD, such as immobility (decrease of spontaneous motor activity), tremor, muscle rigidity, and postural dysfunction, in conjunction with dopaminergic degeneration of the substantia nigra [ 22 , 24 ]. Furthermore, in MRI studies of MPTP-treated marmosets, voxel-based morphometry has revealed a decreased local tissue volume in the substantia nigra, and diffusion-tensor imaging demonstrated fiber loss in the nigrostriatal pathway [ 25 , 26 ].…”
Section: Experimental Disease Models For Translational Research Using...mentioning
confidence: 99%